Latihan Menghafal Hadist Menggunakan Metode Gerakan Kelompok B Di RA Al-Hijrah - Nur Aida; Saudah Saudah; Nurul Wahdah; Muzakki Muzakki (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
This service was motivated by the low ability to memorize hadiths for group B children at RA Al Hijrah. This can be seen in terms of ongoing learning, teachers never apply the habit of reading short hadiths every day so that children are not yet able to memorize the hadith reading, while learning by applying the habit of reading hadiths is very good for young children. The aim of this research is to practice memorizing hadiths using the movement method at RA Al-Hijrah Hampalit Village. This research method uses a participant active learning approach in order to maximize their abilities through a movement method. The subjects in this study were children from group B RA Al-Hijrah, which consisted of 9 children. The results of the training to memorize hadiths using the group B movement method at Ra Al-Hijrah showed an increase in children's activeness and motivation in memorizing daily hadiths with movement.